Three-dimensional finite element analysis of initial displacement and stress on the craniofacial structures of unilateral cleft lip and palate model during protraction therapy with variable forces and directions. Issue 16 (9th December 2020) - Parveen, Shahistha; Husain, Akhter; Gosla Reddy, Srinivas; Mascarenhas, Rohan; Shenoy, Satish
Abstract: Maxillary protraction and expansion is recommended to treat midfacial deficiency in patients with cleft lip and palate (CLP), where amount and direction of forces can change displacement and stress. This study assessed the initial displacement and stresses using Facemask and Maxgym forces with and without RME at +20 ∘, 0 ∘, and -20 ∘ angulation using a finite element (FE) model of unilateral cleft lip and palate (UCCLP). The Initial displacement and stress were more for protraction with expansion as compared to only protraction. Asymmetric displacement was observed with more on cleft than on noncleft side and more on dental than skeletal structures. Palatal plane rotated less upward, increased arch width and decreased arch length was observed with protraction with expansion.